Screening for refractive errors at age 1 year: a pilot study. Issue 4 (April 1979) - Ingram, R M; Traynar, M J; Walker, C; Wilson, J M
Abstract : Cycloplegic refraction of 1-year-old children is technically possible and is acceptable to mothers as a method for screening children for visual defects. The range of refractions found in a sample of 186 1-year-old children is reported. Prediction of which children are significantly at risk for squint and/or amblyopia is possible on the basis of refractions at age 1 year according to the criteria selected for an 'abnormal' refraction. Bilateral hypermetropia and/or astigmatism or anisometropia at age 1 year was significantly (P less than 1 in 10 000) associated with a child eventually being found to have squint or amblyopia. Both the age of screening and criteria of abnormality will probably need modification. +2.50 or more D hypermetropia in any one meridian of either eye at age 1 year was even more significantly (P = 0.000 000 05%) associated with squint and/or amblyopia. The possibility that meridional hypermetropia could be the basic defect in squint and amblyopia is discussed.